2015
DOI: 10.1002/ccd.25780
|View full text |Cite
|
Sign up to set email alerts
|

Interoperator and intraoperator (in)accuracy of stent selection based on visual estimation

Abstract: Visual estimation of coronary lesion length has a high degree of variability, which may lead to inappropriate stent selection. Improving the accuracy of lesion length measurement may improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…This study confirms and expands on previous studies that indicate that visual estimate assessment of coronary lesion length has a high degree of inaccuracy [7][8][9][10][11][12]. This study also demonstrates the utility and ease of using the objective measurement functions built into the R-PCI system.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms and expands on previous studies that indicate that visual estimate assessment of coronary lesion length has a high degree of inaccuracy [7][8][9][10][11][12]. This study also demonstrates the utility and ease of using the objective measurement functions built into the R-PCI system.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have shown that there is a high degree of inter-rater and intra-rater variability associated with visual assessment of stenosis severity when compared to objective measurement techniques [7][8][9][10][11]. A recent survey study of 40 interventional cardiologists comparing visual estimate to qualitative coronary angiography (QCA) showed that visually estimated lesion length was accurate in only 30% of the cases, which lead to both the selection of overly long and overly short stents in 23% and 24% of the cases, respectively [12].…”
Section: Introductionmentioning
confidence: 94%
“…Percutaneous coronary intervention (PCI) is currently indicated for flow‐limiting coronary lesions associated with myocardial ischemia when guideline‐directed medical therapy is expected to have suboptimal outcomes and/or fails to control ischemic symptoms . Angiography (ANGIO) alone is limited by both intraobserver and interobserver variability and inability to determine the hemodynamic significance of intermediate coronary lesions (40–70% stenosis range) .…”
Section: Introductionmentioning
confidence: 99%
“…With conventional PCI, it is known there is a high degree of inter‐operator variability in the visual assessment of coronary lesion length which may in turn portend higher rates of geographic miss . Contrastingly, the CorPath 200 system has the ability to capture computer‐guided measurements of lesions lengths during guidewire advancement and has been associated with a reduced incidence of geographic miss.…”
Section: Advantages Of Robotic‐assisted Pci Compared With Manual Pcimentioning
confidence: 99%